Efforts to Improve English Learning Outcomes by Implementing Project-Based Learning Models Online - Surya Sagiro Batubara (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This classroom action research was conducted to find out how the implementation of Project-Based learning online improves English learning outcomes in Kelas IX-A in SMP Negeri 15 Cirebon. This is a descriptive qualitative study done in two cycles with 24 students as participants, and the researcher herself acted as a participant observer. Data collection did by observation and document analysis, and the findings were then analyzed qualitatively based on the relevant theories explained in this study. The results show that the implementation of Project-Based learning online is significant to improve students' ability in writing simple fairytales in Kelas IX-A in SMP Negeri 15 Cirebon. However, teachers who implement this model need to give maximum motivation and material enrichment to increase students’ confidence and participation during the learning process. To better perform this model online, teachers need to have great classroom management skills and master digital teaching. Further study in a larger scope is recommended for better results.